Isopolymolybdic acid hybrid resistive random access memory material based on tetraphenyl ethylene molecules and preparation method and application thereof
The preparation of homopolymolybdate hybrid storage material based on tetrastyrene molecules by thermal solvent method, solving the problems of poor device morphology, poor repeatability and complex synthesis process in the prior art, and achieving multi-stage controllable memory storage and high temperature resistance, which is suitable for the application of multi-stage memristors.
Patent Information
- Application Number
- CN202411771561.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The prior art faces problems such as poor device morphology, poor repeatability, and complex synthesis process when manufacturing multi-level memory, making it difficult to realize high-density data storage.
Using the hot solvent method, 4-[4-(1,2,2-triphenylvinyl)phenyl]pyridine and [(n-C4H9)4N]4(Mo8O26) were used as raw materials to prepare a homopolymolybdate hybrid storage material based on tetrastyrene molecules. This method is simple and easy to operate, the raw materials are easy to obtain, and the preparation process is free of harmful products, making it suitable for green synthesis.
The prepared material is a multi-stage controlled memory storage material, suitable for multi-stage memristors, showing good multi-stage memory storage performance and high temperature resistance, and is suitable for large-scale industrial production.
Smart Images

Figure CN119684618A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of storage materials, and in particular relates to a homopolymolybdic acid hybrid type resistive storage material based on tetraphenylethylene molecules, and a preparation method and application thereof. Background Art
[0002] The era of rapid expansion of information has put forward higher requirements for the next generation of high-density data storage, and multi-level memory is the most practical way to break through the von Neumann bottleneck. In order to achieve high-density data storage, it is crucial to study new materials. Since organic-inorganic hybrid materials have a controllable structure, the resistance switching behavior can be significantly enhanced through subtle structural modifications and designs. However, it also has certain limitations. The manufacturing process of the device often faces problems such as poor device morphology, poor repeatability, and complex synthesis process. Summary of the invention
[0003] In order to solve the above problems, the present invention proposes a homopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules and a preparation method and application thereof. The method uses 4-[4-(1,2,2-triphenylvinyl)phenyl]pyridine and [(n-C4H9)4N]4(Mo8O 26 ) as raw material, adopts hot solvent method, the preparation method is simple and easy to operate, the raw materials are easy to obtain, easy to realize, and there are no harmful products in the preparation process. It is an environmentally friendly green synthesis. The prepared isopolymolybdic acid hybrid resistive storage material based on tetraphenylethylene molecules is a multi-level controllable memory storage material, which can be used in multi-level memristors.
[0004] The present invention adopts the following technical solutions:
[0005] A method for preparing a homopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules, wherein the specific preparation process is as follows: dissolving a mixture of 0.05 mmol of homopolymolybdic acid and 0.1 mmol mol of tetraphenylethylene molecules in 10 mL of water, stirring for 2 h, and adjusting the pH to 5.0 with HCl to obtain a mixed solution; then moving the mixed solution to a 25 mL stainless steel reactor lined with polytetrafluoroethylene, reacting at 160° C. for 3 days, and obtaining colorless block crystals after cooling, and filtering, washing and drying to obtain the homopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules.
[0006] Preferably, the isopolymolybdic acid is [(n-C4H9)4N]4(Mo8O 26 ); the tetraphenylethylene molecule is 4-[4-(1,2,2-triphenylvinyl)phenyl]pyridine.
[0007] Preferably, the cooling process is: reducing the temperature to 30° C. in 2 days.
[0008] Preferably, the washing agent is distilled water; and the drying is performed by vacuum drying at a temperature of 40°C.
[0009] A homopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules is prepared by using the preparation method of the homopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules.
[0010] An application of a homopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules. The homopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules is used as a resistive memory layer and is applied to a multi-level memristor.
[0011] Preferably, the structure of the multi-level memristor is a sandwich structure consisting of a bottom electrode, a resistive storage layer and a top electrode; the bottom electrode is a fluorine-doped indium tin oxide conductive material; and the top electrode is an inert metal material.
[0012] After adopting the above technical solution, the present invention has the following advantages compared with the background technology:
[0013] 1. The present invention is based on aggregation-induced molecules (AIE) with aggregation-induced current effect and polyoxometalate molecules (POM) with redox properties and high temperature resistance to prepare a homopolymolybdic acid hybrid resistive storage material based on tetraphenylethylene molecules, which is a multi-level switch controllable storage material.
[0014] 2. The present invention uses 4-[4-(1,2,2-triphenylvinyl)phenyl]pyridine (or TPE-mono-Py) and [(n-C4H9)4N]4(Mo8O 26 ) is used as raw material and a hot solvent method is adopted. The preparation method is simple and easy to operate, the raw materials are easily available and easy to implement, and there are no harmful products in the preparation process. It is an environmentally friendly green synthesis with low synthesis cost and excellent film-forming property. It is suitable for large-scale industrial production and has good application prospects.
[0015] 3. The isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules of the present invention can form a uniform and dense film on the substrate, and shows excellent multi-level memory storage performance at room temperature and high temperature conditions, and has good cycle fatigue resistance. The FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag device shows typical non-volatile WORM ternary storage characteristics at room temperature, and its ON2 / ON1 / OFF state current ratio is 10 6.7 :10 4.3 :1,V Set1 / V Set2The device storage behavior shows typical non-volatile WORM ternary storage characteristics at 240℃, and the ON2 / ON1 / OFF state current ratio is 10 5.0 :10 3.2 :1,V Set1 / V Set2 The device was tested at 240℃ and returned to room temperature. The device still showed typical ternary storage characteristics, which verified that the memory device has good device stability and provided a new strategy for the preparation of high-performance memory with high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The crystal structure diagram of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules of the present invention.
[0017] Figure 2 This is an X-ray powder diffraction pattern of the isopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules of the present invention.
[0018] Figure 3 This is the infrared spectrum of the isopolymolybdic acid hybrid type resistive storage material based on tetraphenylethylene molecules of the present invention.
[0019] Figure 4 This is a liquid ultraviolet-visible diffuse reflectance spectrum of the isopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules of the present invention.
[0020] Figure 5 This is a thermogravimetric diagram of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules of the present invention.
[0021] Figure 6 It is a schematic diagram of the preparation process of the isopolymolybdic acid hybrid type resistive memory material device based on tetraphenylethylene molecules of the present invention.
[0022] Figure 7 This is a test diagram of the IV characteristic curve of the isopolymolybdic acid hybrid type resistive memory material device based on tetraphenylethylene molecules of the present invention at room temperature.
[0023] Figure 8 This is a test diagram of the IV characteristic curve of the isopolymolybdic acid hybrid type resistive memory material device based on tetraphenylethylene molecules of the present invention at 240°C.
[0024] Fig. 9 This is a test diagram of the IV characteristic curve of the isopolymolybdic acid hybrid type resistive memory material device based on tetraphenylethylene molecules of the present invention when the high temperature returns to room temperature. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0026] See also Figures 1 to 9 .
[0027] Preparation of a tetraphenylethylene-based isopolymolybdic acid hybrid resistive memory material:
[0028] [(n-C4H9)4N]4(Mo8O 26 A mixture of 2-(4-(1,2,2-triphenylethylene)phenyl)pyridine (0.041g, 0.1mmol) was dissolved in 10mL of water, stirred for 2h, and the pH was adjusted to 5.0 with HCl (1mol / L). The resulting mixed solution was further moved to a 25mL stainless steel reactor lined with polytetrafluoroethylene, kept at 160°C for 3 days, and then cooled to 30°C over a 2-day program. Colorless block crystals were obtained, filtered, washed with distilled water, and vacuum dried at 40°C to obtain 0.0243g of product, that is, a homopolymolybdic acid hybrid resistive storage material based on tetraphenylethylene molecules was obtained.
[0029] First, place the FTO conductive glass in a beaker and add acetone, ethanol and deionized water in turn, and perform ultrasound for 20 minutes respectively. Use an oven drying at 100°C for 30 minutes to dry the FTO (20mm×20mm). Secondly, add the crystal to be tested (5mg) to DMF (10mL), and form a clear solution after ultrasound for 2h. Then take 0.2mL of the solution and drop it on the conductive surface of the conductive glass. Spin coating at 1000rpm, 3000rpm and 5000rpm for 10s respectively, and then anneal at 60°C for 3h to remove the DMF solution. Finally, use 0.5mg·mL -1 The top silver electrodes of all devices were prepared by passing a Ag nanowire suspension of 20% concentration through a mask with small circular holes of about 0.1 cm in diameter for 1 min, and the prepared devices were placed in an oven at 60°C for 30 min to improve their adhesion.
[0030] Performance Testing:
[0031] 1. The crystal structure of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules Figure 1 As shown. Figure 1 It can be seen that the structural analysis of the isopolymolybdic acid hybrid resistive switching memory material based on tetraphenylethylene molecules shows that the compound is composed of two parts: one (Mo8O 26 )4- Anion, four (TPE-mono-Py) + The molybdate anion forms a zero-dimensional molecule with four organic cations through electrostatic attraction and belongs to the triclinic P-1 space group. 2h Symmetrical, composed of eight MoO6 octahedrons sharing oxygen vertices, Mo is located at the center of the octahedron, connected to four bridging oxygens, one terminal oxygen and one central oxygen atom. The length is within the normal range, and the dihedral angles between the two organic cationic pyridine rings and their adjacent benzene rings in the asymmetric unit are 29.34° and 28.76°, respectively, indicating that there is a certain degree of distortion between the rings (e.g. Figure 1 Part a in the figure). The free water molecules in the crystal interact with the two (Mo8O 26 ) 4- Anion connected, (TPE-mono-Py) + The pyridine ring of the cation is hydrogen bonded to a free water molecule and a (Mo8O 26 ) 4- Anion-linked (eg Figure 1 (Part b). (TPE-mono-Py) + The CH···π interaction between the benzene rings of the cation increases the structural stability of the organic part. (Mo8O 26 ) 4- The anion interacts with (TPE-mono-Py) through anion···π + The pyridine ring in the cation attracts and further increases the stability of the overall structure (such as Figure 1 Due to the existence of hydrogen bonds in compound 2-1, the interaction between CH···π and anion···π (such as Figure 1 Part c), the stability of the overall architecture has been enhanced, and the 3D stacking diagram of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules is shown in Figure 2. Figure 1 As shown in part e. Table 1 is the crystallographic data and structural refinement parameters of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules. Table 2 is the hydrogen bond length and bond angle table of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules. Table 3 is the CH···π interaction table of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules. Table 4 is the anion···π interaction table of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules.
[0032] Table 1: Crystallographic data and structural refinement parameters of tetraphenylethylene-based isopolymolybdate hybrid resistive memory materials
[0033]
[0034]
[0035] Table 2: Bond length and bond angle of hydrogen bonds in isopolymolybdic acid hybrid resistive memory materials based on tetraphenylethylene molecules
[0036]
[0037]
[0038] Table 3: CH···π interaction table of homopolymolybdic acid hybrid resistive memory materials based on tetraphenylethylene molecules
[0039]
[0040] Symmetry code: a -x+1,-y,-z; b -1+x,y,z; c -x,1-y,1-z
[0041] Table 4: Anion···π interaction table of homopolymolybdate hybrid resistive switching memory materials based on tetraphenylethylene molecules
[0042]
[0043] Symmetry code: a 1-x,2-y,1-z
[0044] 2. X-ray powder diffraction analysis
[0045] like Figure 2 As shown in the figure, the X-ray powder diffraction pattern of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules, the experimental value and the fitting value are consistent, the results show that the compound is a pure phase, and the difference in intensity of some diffraction peaks is caused by the coarseness and anisotropy of the crystal grinding.
[0046] 3. Infrared spectrum characterization:
[0047] like Figure 3 As shown in the figure, the infrared spectra of the homopolymolybdate hybrid resistive memory materials based on tetraphenylethylene molecules. Since the organic parts of the three compounds are mainly tetraphenylethylene, the substituents are pyridine or imidazole, and the inorganic part is molybdate anion. In the infrared spectrum, the -1 The stretching vibration of the CN bond is at 1000-500cm -1The vibration peaks in the region are attributed to the Mo-O asymmetric stretching vibration in the molybdate anion. The main infrared peak positions and their attributions of the isopolymolybdate hybrid resistive switching memory materials based on tetraphenylethylene molecules are shown in Table 5.
[0048] Table 5: Main infrared spectral characteristic absorption peaks and their attributions of isopolymolybdic acid hybrid resistive memory materials based on tetraphenylethylene molecules
[0049]
[0050] 4. Liquid UV diffuse reflectance spectroscopy analysis
[0051] The liquid UV-visible diffuse reflectance spectrum of the isopolymolybdate hybrid resistive memory material based on tetraphenylethylene molecules was tested in the wavelength range of 200-800nm. Figure 4 As shown. It was found that the absorption peaks of the three compounds at 250-320nm were attributed to the π-π * The strong absorption peak near 340nm is attributed to the charge transition of O→Mo.
[0052] 5. Thermogravimetric analysis
[0053] like Figure 5 As shown, in a nitrogen atmosphere, the heating rate was 10°C / min, the test temperature range was 30-800°C, and the three compounds were subjected to thermogravimetric tests. The test results are shown in Figure 2-8 As shown. The crystal structure of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules can be maintained up to 270°C. In the first stage of heating (30-130°C), the weight loss ratio is 1.00% (theoretical value is 1.26%), which is attributed to the loss of free water in the crystal. In the second stage, 130-275°C, the weight loss ratio is 3.93% (theoretical value is 4.02%), which is attributed to the loss of pyridine rings on organic ligands. In the third stage, 275-500°C, the weight loss ratio is 54.16% (theoretical value is 58.46%), which is mainly attributed to the loss of organic matter in the compound.
[0054] 6. Multi-level controllable memory storage performance test:
[0055] The IV characteristic curve of FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag device was tested in the KEYSIGHT-B2901A single-channel semiconductor parameter tester.
[0056] like Figure 7The figure shows the electrical characteristics of FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag at room temperature. First, the FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag memory device is tested for the current-voltage (IV) characteristic curve of 0V→5V→0V→-5V under a 0.5A limiting current (CC). Figure 7 As can be seen in part a, when a forward sweep voltage (from 0 to 5.0 V) is applied, the device is initially in a low conductivity (“0” or “off”) state. When the forward voltage is increased to 0.99 V, the device switches from a low conductivity (~10 -8.5 A, "off" state) to medium conductivity (~10 -4.1 A, "ON1" state). Later, when the applied forward voltage is increased to 1.23 V, the "ON1" state switches to a high conductivity state (~10 -1.7 A, "ON2" state). This process is equivalent to the "write" process in digital storage. In the subsequent 5-0V and 0-5V scans of the applied voltage, the device remains stable in the high conductivity state, which is equivalent to the "read" process in digital storage. For the ON2, ON1, and OFF states, the corresponding current ratio is 10 6.7 :10 4.3 :1, higher than the switching current ratio of organic devices, such as imide polymer: ITO / 2DP / Ag (ON2 / ON1 / OFF=10 3 :10:1), all-inorganic graphene oxide device: ITO / GO-based / Ni (ON2 / ON1 / OFF=10 3 :10 2 :1). The data results show that the device exhibits typical non-volatile WORM ternary storage characteristics. Figure 7 It can be seen from part b that at constant voltages of 0.01V, 1.37V, and 1.97V, ON2, ON1, and OFF have good stability and no obvious deviation occurs. Figure 7 Part c of the V of 10 rounds of measurement data Set1 and V Set2 Statistics were performed and a bar graph was made based on the distribution characteristics. The results showed that the ternary storage performance of the device has good repeatability. Figure 7 As shown in part d, 10 random IV characteristic curves are used to make a waterfall diagram to verify the ternary storage stability of the device. Figure 7As shown in part e, the stability of the memory device is further verified by taking 100 rounds of high and low resistance state current distribution scatter plots at 0.01V voltage. And through the statistics of 100 rounds of IV characteristic curves, the ternary yield of the device is 70%, which is higher than the ternary memory yield of most devices, such as covalent organic polymer: ITO / Py-COPs / Ag (55%), inorganic metal ion organic coordination polymer ITO / Pd-DABDT / Al (56%). Retention time is a key parameter for device stability, such as Figure 7 As shown in the middle f part, under the 0.1V constant voltage, the device is in the "OFF", "ON1", and "ON2" states for 3×10 3 s has not changed significantly.
[0057] like Figure 8 The figure shows the electrical characteristics of FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag at 240°C. The current-voltage (IV) characteristic curve test of FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag memory device under 0.5A limiting current (CC). Figure 8 As can be seen in part a, when a forward sweep voltage (from 0 to 5.0 V) is applied, the device is initially in a low conductivity (“0” or “off”) state. When the forward voltage is increased to 0.89 V, the device switches from a low conductivity (~10 -6.8 A, "off" state) to medium conductivity (~10 -3.6 A, "ON1" state). Later, when the applied forward voltage is increased to 1.47 V, the "ON1" state switches to a high conductivity state (~10 -1.8 A, "ON2" state). This process is equivalent to the "write" process in digital storage. In the subsequent 5-0V and 0-5V scans, the device remains stable in the high conductivity state, which is equivalent to the "read" process in digital storage. For the ON2, ON1, and OFF states, the corresponding current ratio is 10 5.0 :10 3.2 :1, indicating that the device exhibits typical non-volatile WORM ternary storage characteristics. Figure 8 It can be seen from part b that at constant voltages of 0.01V, 1.14V, and 1.89V, ON2, ON1, and OFF have good stability and no obvious deviation occurs. Figure 8 Part c performs V on 10 rounds of measurement data. Set1 and V Set2 The statistics are made into a bar chart based on the distribution characteristics. The results show that the ternary storage performance of the device has good repeatability. In addition, Figure 8As shown in part d, 10 random IV characteristic curves are used to make a waterfall diagram to verify the ternary storage stability of the device. Figure 8 As shown in part e, the stability of the memory device is further verified by taking 100 cycles of high and low resistance state current distribution scatter plots at a voltage of 0.01V, indicating that the device can operate stably at 240°C, which is much higher than the tolerance temperature of other materials, such as organic-inorganic halide perovskite: Ag / BA2PbI4 / Pt / Ti / SiO2 / Si (87°C), organic polymer: Al / SWNT+PS-b-PPP / Au (100°C). Figure 8 The device shown in part f can achieve a maximum current switching ratio of 10 at a high temperature of 240°C. 5 .
[0058] like Fig. 9 The figure shows the electrical characteristics analysis of FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag from high temperature back to room temperature. The current-voltage (IV) characteristic curve test of FTO / isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules / Ag memory device under 0.5A limiting current (CC). Fig. 9 It can be observed that at 240°C the device exhibits typical ternary storage characteristics. When the ambient temperature is restored to room temperature, the device still exhibits typical ternary storage characteristics. This is repeated three times to verify the high-temperature storage stability of the device. It is found that the device has good high-temperature resistance and can withstand high temperatures of 240°C.
[0059] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a homopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules, characterized in that: The specific preparation process is as follows: a mixture of 0.05 mmol of isopolymolybdic acid and 0.1 mmol of tetraphenylethylene molecules is dissolved in 10 mL of water, stirred for 2 hours, and the pH is adjusted to 5.0 with HCl to obtain a mixed solution; the mixed solution is then moved to a 25 mL stainless steel reactor lined with polytetrafluoroethylene, and the reaction is maintained at 160°C for 3 days. After cooling, colorless block crystals are obtained. After filtering, washing and drying, isopolymolybdic acid hybrid resistive storage material based on tetraphenylethylene molecules is obtained.
2. The method for preparing a tetraphenylethylene-based homopolymolybdic acid hybrid resistive memory material according to claim 1, characterized in that: The isopolymolybdic acid is [(n-C4H9)4N]4(Mo8O 26 ); the tetraphenylethylene molecule is 4-[4-(1,2,2-triphenylvinyl)phenyl]pyridine.
3. The method for preparing a tetraphenylethylene-based isopolymolybdic acid hybrid resistive memory material according to claim 1, characterized in that: The cooling process is: the temperature is reduced to 30° C. in 2 days.
4. The method for preparing a tetraphenylethylene-based homopolymolybdic acid hybrid resistive memory material according to claim 1, characterized in that: The washing agent is distilled water; the drying is vacuum drying at 40°C.
5. A homopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules, characterized in that: The isopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules is prepared by the preparation method of the isopolymolybdic acid hybrid type resistive memory material based on tetraphenylethylene molecules as described in any one of claims 1 to 4.
6. An application of the isopolymolybdic acid hybrid resistive memory material based on tetraphenylethylene molecules as claimed in claim 5, characterized in that: The isopolymolybdate hybrid type resistive memory material based on tetraphenylethylene molecules is used as a resistive memory layer and is applied to a multi-level memristor.
7. The use of a tetraphenylethylene-based isopolymolybdic acid hybrid resistive memory material as claimed in claim 6, characterized in that: The structure of the multi-level memristor is a sandwich structure consisting of a bottom electrode, a resistive storage layer and a top electrode; the bottom electrode is a fluorine-doped indium tin oxide conductive material; and the top electrode is an inert metal material.
Citation Information
Patent Citations
Isopolymolybdate organic-inorganic hybrid compound and preparation method thereof
CN105153203A
Tetraphenylethylene blue-fluorescence organic compound, preparation method thereof and blue organic electroluminescence device
CN108530258A
Mixed isopolymolybdate organic-inorganic hybrid material and preparation method and application thereof
CN111450890A
Molybdenum telluride-based memristor and preparation method thereof and nonvolatile memory
CN112331766A
Polyacid-based metal organic framework material used as active layer of high-temperature resistive random access memory
CN113136036A